Biblical conceptual sphere as a concept of Taras Shevchenko’s idiostyle and its reverbalization in Ukrainian bible translations - Dzera , Oksana (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article elaborates the analysis of Ukrainian translations of the Holy Scripture through the prism of Shevchenko’s metabiblical images. Biblical conceptual sphere is defined as a fragment of biblical picture of the world shaped on the basis of Old Hebrew, less frequently Old Greek imagery and represented by the totality of concepts which are connected through overlapping, interrelation, hierarchy and opposition and are thematically grouped. Verbalizers of biblical concepts contain the complex accumulation of senses reflecting correlations between God and people through specific world perception of ancient Hebrews. The mediating link between the Bible prototext and biblical metatexts is created by national translations of the Holy Scripture that shape national biblical conceptual spheres via multiple deviations of the Hebrew and Greek sources. The deviations affect national phraseology as well as individual authors’ interpretations of the Book of Books. Special attention is devoted to recursive deviation which manifests itself when a national biblical conceptual sphere and even national translations of the Bible contain elements of authors’ biblical intertexts. Taras Shevchenko’s poetry is viewed as the primary Ukrainian recursive biblical intertext. His idiostyle is characterized by the verbalization of biblical concepts through overlapping biblical and nationally-bound senses. Metabiblical images of Shevchenko’s idiostyle are tracked down to the Bible translation done by I. Khomenko and edited by I. Kostetskyij and V. Barka. The editors who represented the baroque tradition of the Ukrainian translation domesticated Khomenko’s version and introduced into it elements of the Ukrainian metabiblical conceptual sphere, predominantly Shevchenko’s metabiblical images. I. Khomenko himself did not approve of this strategy and regarded it as a violation of the Word of God. Yet the monastic order of St. Basil the Great that commissioned this translation did not consult the translator before publishing its edited version. Similar domesticating strategy is observed in the first Ukrainian complete translation of the Bible done by P. Kulish, I. Puluj, and I. Nechuj-Levycjkyj in 1903. Shevchenko’s influence is particularly felt in epithets specifying key biblical images, such as enemy (лютий / fierce) and heart (тихе / meek). Though each book of the Holy Scripture in this translation is ascribed to only one translator of the three it seems logical to surmise that P. Kulish, the founder of the baroque translation tradition in Ukraine, was the first to draw images from Shevchenko’s metabiblical conceptual sphere. The article postulates the necessity to perceive Shevchenko’s poetry as a complete Biblical intertext which not only interprets national biblical canon but also generates it.